Consumer Acceptance of Orange Juice Mixed with Water Mint Leave Extract - Ali, Marwa R. (Recent Patents on Food, Nutrition & Agriculture, 2018)
Aims and Background: Aseptic processing is focused only fruit juices, but the processing of strengthful fruit, like fruit juice fortified with other beneficial herbs by tetrapack processing has not been attempted. The aim of the study to introduce a new form of orange juice with a good nutritional value. Materials and Methods: Orange-Mint leaves juice was formulated using different addition percentages of mint leaves extract. The juice was aseptically processed, packed in glass bottles under sterilized environment and sterilized at 70°C for 15min then storage at 5°C for 3 months. All of the properties of juice “physicochemical, nutritional values, microbiological and sensory” was determined. Results: The results showed that there was no difference in pH, total soluble solids, ash, and total acidity in all samples moreover, the orange juice with 15% of mint leaves extract recorded the best values of sensory evaluation, on the other hand, it was recorded lower values of vitamin C and total phenolic compound than fresh or pasteurized orange juice because of increasing in addition % of mint leaves extract to orange juice. The sensory properties of juice samples were not remarkable any changes during storage. The results indicated that the juice had a good acceptability up to 3 months of storage at 5°C. Conclusion: Now, the consumer is interested with nutritional and healthy foods, because functional foods reduce the health problems, as described in various patents. So, the Orange-Mint leaves blended juice will be a good option for the consumer.
Keywords: peppermint